Case Report: Diazoxide-induced diabetic ketoacidosis in a patient with insulinoma - Run Ting Chin; Jolene Jiayu Kiew; Khek Yu Ho; Doddabele S. Deepak (Frontiers in Endocrinology)
Definitive management of insulinoma is challenging as curative surgery is associated with a considerable risk of morbidity and mortality. The successful long-term use of diazoxide for patients diagnosed with insulinoma has been described, but rarely, the use of diazoxide can be complicated by diabetic ketoacidosis (DKA). This case report describes a frail elderly patient with high surgical risk diagnosed with pancreatic head insulinoma whose initial treatment with diazoxide was complicated by a hyperglycemic crisis. Her insulinoma was eventually managed with endoscopic ultrasound-guided-radiofrequency ablation (EUS-RFA) with complete resolution of hypoglycemic episodes. This case highlights the importance of monitoring for side effects of diazoxide, especially in the elderly, and the role of EUS-RFA as an emerging non-surgical treatment modality for insulinoma.